Digital Living Qur’an and Audience Engagement with Riko The Series on YouTube in Indonesian Muslim Family Contexts - Talin Salsa Bila; Fajar Rohandy; Izzah Faizah Siti Rusydati Khaerani; M. Solahudin; Yayan Mulyana (UIN Sunan Gunung Djati Bandung, 2026)
Purpose: This study aims to analyse audience engagement with Qur’anic content in Riko The Series on YouTube as a digital form of Living Qur’an. It examines how Qur’anic values are received, interpreted, and reproduced by audiences through comment culture, digital traces, interaction, and family-based viewing practices. Methodology: This study employed a qualitative netnographic design. The data were collected from three selected episodes of Riko The Series, thirty purposively selected YouTube comments, digital engagement metrics, semi-structured interviews with six audience informants, and one interview with a member of the production team. The data were analysed through four netnographic dimensions: digital cyberculture, digital traces, audience interaction, and immersive engagement. Findings: The findings show that the comment space of Riko The Series contains Islamic invocations, Qur’anic references, hadith citations, prayers, moral advice, and personal reflections. Digital trace data reveal different engagement patterns across episodes: Kambing Putih Riko generated the highest views and likes, while Tanaman Bertasbih produced the highest number of comments. Interview data further show that the series encouraged Qur’anic reflection, children’s imitation of Islamic expressions, parent-child religious discussion, and audience feedback for future content development. Implications: This study suggests that Islamic animation can support informal Qur’anic learning within Muslim families when accompanied by parental mediation, reliable references, and careful comment moderation. Originality: The originality of this study lies in its netnographic analysis of audiences as active digital actors who participate in producing and circulating Qur’anic meanings through YouTube-based Islamic animation.